MODELS OF LOSSES OF WORKABILITY OF SOCIO-ECONOMIC SYSTEMS - Betskov , Aleksandr; Nikitina, Marina; Yanova , Svetlana; Oleynik , Aleksandr; Kilyaskhanov, Hizri; Grischenko , Leonid; Niyazbekova , Shakizada (Revista Inclusiones, 2020)
In the process of transformation of the socio-economic system, the sustainability of the system is particularly relevant. Under the influence of internal and external threats, the sustainability of the socio-economic system may be impaired. This probably could lead to a complete loss of the entire system. The aim of the study is mathematical and graphical modeling of the loss of efficiency of socioeconomic systems. To achieve this goal, the following tasks were solved: a mathematical model of the loss of efficiency of the socio-economic system is presented; a graphical interpretation of the model of the loss of efficiency of the socio-economic system is presented. According to the results of modeling the loss of working capacity of the socio-economic system, two equations were obtained. The equations described the loss of working capacity of the socio-economic system when exposed to any variable regime of factors. A graphical interpretation was also presented. Mathematical and graphical modeling of the working capacity of a socio-economic system allows, in the conditions of transformation of a socio-economic system, to determine with mathematical precisión the moments of failure and the complete loss of system performance. This is the fundamental basis for making decisions about maintaining system stability